Pengembangan Media Pembelajaran Interaktif Prezi untuk Menumbuhkan Karakter Rasa Ingin Tahu - Tohir Solehudin; Retno Triwoelandari; Ahmad Mulyadi Kosim (Indonesian Journal of Learning Education and Counseling, 2020)
This Research aims to: 1) determine the feasibility of interactive learning media prezi on the subjects of Islamic Religious Education (PAI) and 2) determine the effectiveness of interactive learning media prezi in islamic education in grade 8 of JUNIOR high school to cultivate the character of the curiosity of the students. This research using methods Research and Development (R&D). Instruments of data collection using observation sheets and angketPada stage of development, the results of the research show numbers matter experts 82.89%, media experts 79.42%, and language expert 76.39%. At the stage of testing, limited testing shows the number of 81.61%. The results of the final testing, extensive trials showed sig. 0.00 < 0.05 with the difference of the results of the class experiment 39.58 and the control class 24.87 with the difference of the results amounted to 14.71. Thus, the development of interactive learning media Prezi as a medium of teaching the PAI be used to grow the characters curiosity of students.